2016
DOI: 10.3390/ijms17101522
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12/CXCR4 Axis Regulates Aggrecanase Activation and Cartilage Degradation in a Post-Traumatic Osteoarthritis Rat Model

Abstract: We evaluated the role of the CXCL12/CXCR4 (C-X-C motif chemokine ligand 12/C-X-C chemokine receptor type 4) axis in aggrecanase-mediated cartilage degradation, and explored the underlying mechanism in a post-traumatic osteoarthritis rat model. Expression of CXCL12/CXCR4 and ADAMTS-5 was analyzed in the knees of osteoarthritic and non-arthritic rats using Western blot, ELISA, immunohistochemistry and immunofluorescence. Rodent studies were performed using Sprague-Dawley rats, with animals divided into three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…16) It was reported that CXCL12/CXCR4 axis regulated activation of aggrecanase and degradation of cartilage in a rat model with post-traumatic osteoarthritis. 17) Osteoarthritis could be attenuated via blocking of the SDF-1/CXCR4 signaling pathway 18) . CXCR4 was confirmed to be regulated by microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…16) It was reported that CXCL12/CXCR4 axis regulated activation of aggrecanase and degradation of cartilage in a rat model with post-traumatic osteoarthritis. 17) Osteoarthritis could be attenuated via blocking of the SDF-1/CXCR4 signaling pathway 18) . CXCR4 was confirmed to be regulated by microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against GFAP (ab10062), CXCL12 (ab25117), CXCR4 (ab197203), NeuN (ab104224), and OX42 (ab1211) were purchased from Abcam. Antibodies against CXCR4 (11073‐2‐AP) were purchased from Proteintech (San Ying biotechnology, Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%
“…Cartilage regeneration process that involves recruitment of reparative cells can be negatively affected by antichondrogenic or proinflammatory cells chemoattracted concomitantly to the damaged area. The SDF-1/CXCR4 pathway is known to recruit and activate MSCs in chondrogenic differentiation 47,98 ; however, blocking this pathway to some extent attenuates cartilage pathogenesis by reducing MMP and aggrecanase production stimulated from chondrocytes 99,100 . A recent study shows that engineering chondrocytes to overexpress HMGB1 A-box significantly decreases the IL-1b-stimulated production of MMPs and ADAMTs and suppression of HMGB1/TLR4/NF-kB pathway improves chondrogenesis 101 .…”
Section: Future Prospects For the Regenerative Treatment Of Oamentioning
confidence: 99%